The gut microbiome is a significant risk factor for future chronic lung disease - Liu Yang; Teo Shu Mei; Méric Guillaume; Tang Howard H.F.; Zhu Qiyun; Sanders Jon G.; Vázquez-Baeza Yoshiki; Verspoor Karin; Vartiainen Ville A.; Jousilahti Pekka; Lahti Leo; Niiranen Teemu; et al. (Elsevier Inc., 2025)
Background
The gut-lung axis is generally recognized, but there are few large studies of the gut microbiome and incident respiratory disease in adults.
Objective
We sought to investigate the association and predictive capacity of the gut microbiome for incident asthma and chronic obstructive pulmonary disease (COPD).
Methods
Shallow metagenomic sequencing was performed for stool samples from a prospective, population-based cohort (FINRISK02; N = 7115 adults) with linked national administrative health register–derived classifications for incident asthma and COPD up to 15 years after baseline. Generalized linear models and Cox regressions were used to assess associations of microbial taxa and diversity with disease occurrence. Predictive models were constructed using machine learning with extreme gradient boosting. Models considered taxa abundances individually and in combination with other risk factors, including sex, age, body mass index, and smoking status.
Results
A total of 695 and 392 statistically significant associations were found between baseline taxonomic groups and incident asthma and COPD, respectively. Gradient boosting decision trees of baseline gut microbiome abundance predicted incident asthma and COPD in the validation data sets with mean area under the curves of 0.608 and 0.780, respectively. Cox analysis showed that the baseline gut microbiome achieved higher predictive performance than individual conventional risk factors, with C-indices of 0.623 for asthma and 0.817 for COPD. The integration of the gut microbiome and conventional risk factors further improved prediction capacities.
Conclusions
The gut microbiome is a significant risk factor for incident asthma and incident COPD and is largely independent of conventional risk factors.